Where we have been matters: offering non-traditional students greater opportunities for personal connections to "academic discourse" - O'Neill, Tifarah Hadassah, author; Langstraat, Lisa, advisor; Doe, Sue, committee member; Jennings, Louise, committee member (Colorado State University. Libraries, 2012)
With 73 percent of students now being classified as non-traditional in some way according the U.S Department of Education, it is clear that the student populations at the two year colleges as well as universities are no longer as homogeneous as they were originally. This thesis examines the ways in which non-traditional students may differ in their learning styles and how we as educators can better provide better learning opportunities for these students based upon the works of Malcolm Knowles and other education theorists. This thesis explores the ways non-traditional students are placed within marginalized positions within current university and classroom structures. However, I explore the benefits of creating more inclusive classrooms which value students' external experiences primarily through "hybrid" or personal form of writing. This thesis also explores some of the challenges that can arise when incorporating personal writing into the classroom as well as some pedagogical approaches to combat those challenges.